The Effect of Auction Fee, Administration Fees of State Receivables Management and Management of State-Owned Assets Against Actualization of State Non-Tax Revenue on Kantor Pelayanan Kekayaan Negara dan Lelang Medan Period 2019-2021 - Arthur Simanjuntak; Septony B. Siahaan; Duma Megaria Elisabeth; Yerisma Welly; Dewi Delima Hutagalung (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study examined the effects of auction fees, state receivables management costs, and state property management costs on the realization of non-tax state revenue at the State Asset Service Office and Medan Auction from 2019 to 2021. The Medan KPKNL Performance Achievement Report, which contains the Budget Report and Realization of PNBP for the 2019–2021 year and has a total population of 36, is the population in this research. Due to the large population in this study being relatively small (limited), the sample was chosen using the saturation or census sampling approach. To characterize each variable in this study, this form of research employs a descriptive quantitative technique utilizing secondary data. The Statistical Product and Service Solution (SPSS) Version 25 will process the data. The data analysis method used in this study employs multiple linear regression analysis tests, a coefficient of determination test, a partial hypothesis test (t-test), and a simultaneous test (F test) with a significance level of 0.05. Each variable is stated to have a positive and significant effect on Non-Tax State Revenue based on the results of data analysis tests that have partially been conducted on Auction Fees, Administrative costs for managing state receivables, and Management of state property, and the consequences of research simultaneously stated that all independent variables have an effect positive and significant to PNBP simultaneously with the test results of the coefficient of determination showing in 72.1%.